2014
DOI: 10.1103/physrevlett.112.047005
|View full text |Cite
|
Sign up to set email alerts
|

Local Inhomogeneity and Filamentary Superconductivity in Pr-DopedCaFe2As2

Abstract: We use multi-scale techniques to determine the extent of local inhomogeneity and superconductivity in Ca0.86Pr0.14Fe2As2 single crystal. The inhomogeneity is manifested as a spatial variation of praseodymium concentration, local density of states, and superconducting order parameter. We show that the high-Tc superconductivity emerges from clover-like defects associated with Pr dopants. The highest Tc is observed in both the tetragonal and collapsed tetragonal phases, and its filamentary nature is a consequence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
66
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 41 publications
(53 reference statements)
13
66
0
Order By: Relevance
“…15 [21,25]. However, no evident diamagnetic behavior could be identified in the magnetic susceptibility in the zero-field cool mode, which suggests the filamentary nature of the superconductivity in this material [25]. These properties are qualitatively consistent with previous reports on Ca 1−x Pr x Fe 2 As 2 [15,23,25].…”
Section: Sample Properties and Experimental Setupsupporting
confidence: 90%
See 2 more Smart Citations
“…15 [21,25]. However, no evident diamagnetic behavior could be identified in the magnetic susceptibility in the zero-field cool mode, which suggests the filamentary nature of the superconductivity in this material [25]. These properties are qualitatively consistent with previous reports on Ca 1−x Pr x Fe 2 As 2 [15,23,25].…”
Section: Sample Properties and Experimental Setupsupporting
confidence: 90%
“…We have studied samples with two compositions (x = 0.1 and 0. 15 [21,25]. However, no evident diamagnetic behavior could be identified in the magnetic susceptibility in the zero-field cool mode, which suggests the filamentary nature of the superconductivity in this material [25].…”
Section: Sample Properties and Experimental Setupmentioning
confidence: 85%
See 1 more Smart Citation
“…4. On the other hand, Gofryk et al [22] declared that the high-Tc superconductivity emerges from cloverlike defects associated with Pr dopants according to their abundant observations. At first glance, their proposal seems effective to explain both the broad superconducting transition and the weak diamagnetic signal that detected in the present system.…”
Section: Superconductivity Originmentioning
confidence: 99%
“…And the interface SC origin is supported by the extreme magnetic anisotropy [20], accompanied by an unexpected doping-independent Tc and equally unexpected superparamagnetic clusters associated with As vacancies. Meanwhile, Gofryk et al [22] recently demonstrated the presence of inhomogeneity in the crystal through measuring the spatial variation of the praseodymium (Pr) concentration, local density of states, and superconducting order parameter. They ascribed the high-Tc superconductivity to cloverlike defects associated with Pr dopants.…”
Section: Introductionmentioning
confidence: 99%